Outcome of left atrial appendage closure using cerebral protection system for thrombosis: no patient left behind. Issue 1 (10th December 2021) - Limite, Luca Rosario; Radinovic, Andrea; Cianfanelli, Lorenzo; Altizio, Savino; Peretto, Giovanni; Frontera, Antonio; D'Angelo, Giuseppe; Baratto, Francesca; Marzi, Alessandra; Ancona, Francesco; Ingallina, Giacomo; Capogrosso, Cristina; et al.
Abstract: Background: Left atrial appendage (LAA) thrombosis increases the risk of stroke and its management has to be assessed. The aim of the present study is to evaluate short and long‐term safety and efficacy of a standardized approach of percutaneous LAA closure (LAAC) routinely using a cerebral protection device (CPD) in patients with LAA thrombosis or sludge (LAAT). Methods: We prospectively enrolled 14 consecutive patients with atrial fibrillation complicated by LAAT presenting in a high‐volume tertiary center. In seven patients (50%) LAAT was found after anticoagulant withdrawal for severe bleedings and in the remaining half LAAT was found despite appropriate anticoagulant therapy. All patients were treated with a standardized interventional approach of LAAC routinely using a CPD and guided by transoesophageal echocardiography. Results: Mean age was 68 ± 14 years and nine patients (64%) were male. Mean CHA2 DS2 ‐VASc and HAS‐BLED scores were 3.3 ± 1.6 and 2.3 ± 1.1, respectively. Six patients (42.8%) presented organized thrombi while eight LAA sludge (57.1%). In 13 patients (92.8%) CPD was positioned through a right radial arterial access. Procedural success was achieved in all patients. In one patient we assisted to embolization of the thrombus during deployment of the device in the absence of neurological consequences. During a mean follow up of 426 ± 307 days, one patient died for non‐cardiac cause while no embolic event or major bleeding were reported. Conclusion: In an unselected cohort, LAAC with the systematic use of CPD was a feasible, safe and effective therapeutic option for LAAT both acutely and after long‐term follow‐up.